EVALUASI KEBIJAKAN PENGARUSUTAMAAN GENDER PADA DINAS PEMBERDAYAAN, PERLINDUNGAN ANAK DAN PENGENDALIAN PENDUDUK PROVINSI DKI JAKARTA - Samuel Martua Naibaho; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Gender inequality remains a persistent challenge in public development policies, particularly in regional planning and budgeting processes. To address this issue, the government implements the Gender Mainstreaming (PUG) policy as a strategy to ensure that gender perspectives are integrated into all stages of policymaking. This study aims to evaluate the implementation of gender mainstreaming in DKI Jakarta Province and to identify the factors influencing its effectiveness. The research employs a qualitative approach using the CIPP (Context, Input, Process, Product) evaluation model through in-depth interviews, document analysis, and observation. Research informants consist of regional government officials involved in the implementation of gender mainstreaming. The findings indicate that the implementation of gender mainstreaming in DKI Jakarta has been supported by policy commitment, regulatory frameworks, and coordination mechanisms among regional agencies. However, challenges remain, particularly differences in officials’ understanding of gender perspectives and limited capacity in gender-responsive planning and budgeting. The study concludes that the success of gender mainstreaming implementation is influenced by institutional commitment, human resource capacity, and effective inter-agency coordination